Vibration Transmitted on the Human Body During the Patient’s Ride in a Wheelchair - DZIECHCIOWSKI, Zygmunt Szczepan; KROMKA-SZYDEK, Magdalena (Archives of Acoustics, 2017)
The study investigates the spectra of vibrations transmitted onto the body of a wheelchair user during the ride on typical floor surfaces in public buildings and in their vicinity. Three wheelchair types are considered in the study (universal and active ones). Selected factors are examined that determine the amplitude of vibration acceleration acting upon humans in the analysed frequency range (wheelchair type, user’s body mass, surface type). The spectral analysis gives an insight into some of the factors which lead to a change of the vibration parameters registered at the user’s seat.